OP0171 PHASE 3 TRIAL OF LENABASUM, A CB2 AGONIST, FOR THE TREATMENT OF DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS (DCSSC) - Spiera, R.; Kuwana, M.; Khanna, D.; Hummers, L.; Frech, T.; Stevens, W.; Gordon, J.; Kafaja, S.; Matucci-Cerinic, M.; Distler, O.; Lee, E.B.; Levy, Y.; et al. (Annals of the Rheumatic Diseases, 2021)
Lenabasum is an oral CB2 agonist that attenuates inflammation and fibrosis in SSc animal models and showed clinical benefit with acceptable safety in a Phase 2 trial in dcSSc. Test efficacy and safety of lenabasum in a Phase 3 trial in dcSSc. Subjects ≥18 years old with disease duration ≤ 6 years were randomized 1:1:1 to lenabasum 5 mg, 20 mg, or placebo (PBO), all BID, with stable background immunosuppressant therapy (IST) allowed. The primary efficacy endpoint was ACR CRISS score, and secondary endpoints were ΔmRSS, ΔHAQ-DI, and ΔFVC, all at Week 52 for lenabasum 20 mg vs PBO. 363 adults were dosed; 37 (10%) stopped study drug early, with only 1 subject (PBO cohort) stopping due to adverse event (AE). Baseline demographics were similar among groups. Disease duration was ≤ 3 years in 60% and 66%, mean mRSS score was 22.0 and 23.3, and background IST was used by 89% and 84% of lenabasum 20 mg and PBO groups, respectively. Safety results showed serious AEs and severe AEs occurred in 9.2% and 5.8% vs 14.6% and 13.0%, respectively, of lenabasum 20 mg and PBO groups. Efficacy results (Table) demonstrated: • No significant differences were seen in primary and secondary efficacy endpoints. Primary MMRM analyses with treatment-by-time-by-subgroup interactions showed that background mycophenolate (MMF) significantly influenced the outcome •oSubjects on no IST with disease duration ≤3 years were only 7% of PBO subjects and showed little improvement on PBO, in line with other dcSSc trials in which IST was restricted. Post-hoc subgroup analyses of these subjects on no IST suggested improvement in ΔmRSS and ΔHAQ-DI, for lenabasum 20 mg vs PBO •uUnexpectedly high improvement occurred in PBO subjects receiving IST, notably those on MMF started within 2 years of baseline •nPost-hoc analyses of subjects on established IST (MMF or, if no MMF, ≥ 1 non-MMF IST started > 2 years before baseline) suggested improvement in ΔFVC% (nominal P = 0.0386) and ΔFVC mL (nominal P = 0.0481) for lenabasum 20 mg vs PBO. Improvement in FVC was also seen in subjects on established IST who had ILD at baseline, lenabasum 20 mg vs PBO •mACR CRISS score demonstrated a ceiling effect and correlated most highly with ΔmRSS (r = -0.739) and moderately with MDGA (-0.432), HAQ-DI (-0.362), FVC% (0.366), and PtGA (-0.288) Lenabasum was safely used in this study. Unexpectedly high improvement on background IST, especially MMF, has not been previously reported at this level. The primary endpoint was not met. Post-hoc analyses showed greater improvement in lenabasum- vs PBO-treated subjects who were not on background IST and those on established IST, including subjects with ILD. Robert Spiera Consultant of: Abbvie, Roche-Genetech, GSK, CSL Behring, Sanofi, Janssen, Chemocentryx, Formation Biologics, Mitsubishi Tanabe, Grant/research support from: Roche-Genetech, GSK, Boehringer Ingelheim, Chemocentryx, Corbus, Formation Biologics, Sanofi, Inflarx, Astra Zeneca, Kadmon, Masataka Kuwana Speakers bureau: Boehringer-Ingelheim, Chugai, Janssen, Consultant of: Boehringer-Ingelheim, Chugai, Corbus, Grant/research support from: Boehringer-Ingelheim, Chugai, MBL, Ono Pharmaceuticals, Tanabe-Mitsubishi, Dinesh Khanna Shareholder of: Eicos Sciences, Inc (less than 5%). Leadership/Equity position – Chief Medical Officer, CiviBioPharma/Eicos Sciences, Inc, Consultant of: Acceleron, Actelion, Abbvie, Amgen, Bayer, Boehringer Ingelheim, CSL Behring, Corbus, Gilead, Galapagos, Genentech/Roche, GSK, Horizon, Merck, Mitsubishi Tanabe Pharma, Sanofi-Aventis, and United Therapeutics, Grant/research support from: NIH, Immune Tolerance Network, Bayer, BMS, Horizon, Pfizer, Laura Hummers Consultant of: CSL Behring, Boehringer Ingelheim, Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals. Corbus, Boehringer Ingelheim, Medpace, Kadmon, Cumberland, CSL Behring, Tracy Frech Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals, Wendy Stevens Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals, Jessica Gordon Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals. Research funding for EICOS Pharmaceuticals and Cumberland Pharmaceuticals., Suzanne Kafaja Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals, Marco Matucci-Cerinic Consultant of: Actelion, Janssen, Inventiva, Bayer, Biogen, Boehringer, CSL Behring, Corbus, Galapagos, Mitsubishi, Samsung, Regeneron, Acceleron, MSD, Chemomab, Lilly, Pfizer, Roche, Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals, Oliver Distler Consultant of: Consultancy relationship and/or has received research funding in the area of potential treatments for systemic sclerosis and its complications from (last three years): Abbvie, Acceleron Pharma, Amgen, AnaMar, Arxx Therapeutics, Baecon Discovery, Blade Therapeutics, Bayer, Boehringer Ingelheim, ChemomAb, Corbus Pharmaceuticals, CSL Behring, Galapagos NV, Glenmark Pharmaceuticals, GSK, Horizon (Curzion) Pharmaceuticals, Inventiva, iQvia, Italfarmaco, iQone, Kymera Therapeutics, Lilly, Medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Novartis, Pfizer, Roche, Sanofi, Serodapharm, Topadur, Target Bioscience and UCB., Eun Bong Lee Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals, Yair Levy Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals, Jae-Bum Jun Consultant of: Consultant to Boehringer Ingelheim Korea, Jeil Pharma, Dae Woong Pharma, Kwangdong Pharma, and Sama Pharma., Grant/research support from: Investigator for study sponsored by Corbus Pharmaceuticals, Scott Constantine Employee of: Employee of Corbus Pharmaceuticals, Nancy Dgetluck Employee of: Employee of Corbus Pharmaceuticals, Barbara White Employee of: Employee and stockholder of Corbus Pharmaceuticals, Daniel Furst Consultant of: Corbus, Galapagos, Pfizer, CSL Behring, Mitsubishi Tanabi, Actelion, Amgen, Novartis, Roche/Genentech, Gilead, Talaris, and Boehringer Ingelheim., Grant/research support from: grants from Corbus, Galapagos, GSK, Pfizer, Talaris, CSL Behring, Mitsubishi Tanabi, Christopher Denton Consultant of: Consultancy fees and/or honoraria from Corbus, Actelion, GlaxoSmithKline, Bayer, Sanofi, Galapagos, Inventiva, Boehringer Ingelheim, Roche, CSL Behring, Acceleron, Horizon, Arxx Therapeutics Table 1Primary and secondary efficacy endpoints and post-hoc analyses, Week 52Group, by IST treatmentCohortNΔmRSS, mean (SD)ΔFVC% mean (SD)ΔFVC, mL mean (SD)ΔHAQ-DI mean (SD)ACR CRISS medianmITT population, MMRM primary analysis methodAllPlacebo123-8.1 (7.72)-1.0 (8.68)-51 (317)-0.13 (0.468)0.887Lenabasum 20 mg120-6.7 (6.59)-1.6 (6.91)-78 (265)-0.13 (0.436)0.888Placebo subjects, per protocol completers, LOCFNo ISTPlacebo16-2.3 (9.4)-2.8 (7.4)-97 (244)0.12 (0.34)0.417All ISTPlacebo97-8.9 (7.07)-1.0 (9.2)-43 (330)-0.17 (0.474)0.936MMF, no other ISTPlacebo29-10.7 (8.1)-0.58 (7.1)-37 (235)-0.12 (0.456)0.935MMF ≤ 2 years, no other ISTPlacebo23-11.7 (8.1)-0.3 (6.0)-41 (197)-0.13 (0.495)0.935Non-MMF ≤ 2 yearsPlacebo24-6.7 (6.2)-1.4 (7.87)-52 (281)-0.15 (0.357)0.931Post-hoc comparisons, per protocol completers, LOCFNo ISTPlacebo16-2.3 (9.4)-2.8 (7.4)-97 (244)0.12 (0.34)0.417Lenabasum 20 mg10-6.3 (6.02)-2.3 (5.58)-99 (209)-0.06 (0.498)0.811Established IST1Placebo26-6.1 (5.35)-4.6 (10.11)-170 (350)-0.17 (0.445)0.619Lenabasum 20 mg38-7.4 (5.08)-0.4 (5.70)2-21 (233)3-0.07 (0.357)0.941Established IST, subjects with ILDPlacebo22-5.9 (5.28)-3.7 (5.43)-133 (206)-0.10 (0.372)0.553Lenabasum 20 mg33-7.2 (5.70)-1.0 (10.5)-47 (365)-0.06 (0.391)0.8192 P = 0.0386 two-sample t-test; 3 P = 0.0481 two-sample t-test; other comparisons were not significant